Medical Residents and Interprofessional Interactions in Discharge: An Ethnographic Exploration of Factors That Affect Negotiation - Goldman, Joanne (J Gen Intern Med, 2015)
BACKGROUND: Interprofessional collaboration is an important aspect of patient discharge from a general internal medicine (GIM) unit. However, there has been minimal empirical or theoretical research that has examined interactions that occur between medical residents and other healthcare professionals in the discharge process. This study provides insight into the social processes that shape and characterize such interactions. OBJECTIVE: To explore factors that shape interactions between medical residents and other healthcare professionals in relation to patient discharge, and to examine the opportunities for negotiations about discharge between these professional groups. DESIGN: A qualitative ethnographic approach using observations, interviews and documentary analysis. PARTICIPANTS AND SETTING: Healthcare professionals working in a GIM unit in Canada. APPROACH: Sixty-five hours of observations were undertaken in a range of settings (e.g. interprofessional rounds, medical and nursing rounds, nursing station) in the unit over a 17-month period. A maximum variation sampling approach was used to identify healthcare professionals working in the unit. Twenty-three interviews were completed, recorded and transcribed verbatim. A directed content approach using theories of medical dominance and negotiated order was used to analyze the data. KEY RESULTS: The organization of clinical work in combination with clinical teaching influenced interprofessional interactions and the quality of discharge in this GIM unit. While organizational activities (orientation and rounds) and individual activities (e.g. role modeling, teaching) supported negotiations between medical residents and other healthcare professionals around discharge, participants had varied perspectives about their effectiveness. CONCLUSIONS: This study illuminates social factors and processes that require attention in order to address challenges with interprofessional collaboration and discharge in GIM. These findings have implications for medical education, workplace learning, patient safety and quality improvement.